A Microcontroller-Based Wireless System for Sliding Book Learning Media Tools - Ahmad, Fauzan; Kurnia, Rita; Zakri, Azriyenni Azhari; Pernantah, Piki Setri (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2022)
This design was performed in the development of the Sliding Book learning media tool by utilizing an Arduino UNO R3-based microcontroller control system. The addition of sensors and controllers in the form of Photodiode sensors and infrared remotes is undertaken with the intention of creating a wireless control system. The data is retrieved in the form of voltage data, current data, and the length of time used in one sliding book viewing. The outcome of this study is a sliding book learning media control design with an Arduino-based wireless control system and the addition of an infrared remote sensor and a photodiode sensor. The test results indicate that the command function of the infrared remote works well to provide wireless control of the motor rotation direction of the sliding book tool on the forward, reverse, and stop displays, and when determining the sliding page position, the photodiode sensor function corresponds to the design position of the page boundary reading. Sliding book control average power consumption was shown to be 1.67 Watts for the forward button for a voltage of 5V, 1.68 Watts for 12V and 1.47 Watts for the reverse button for a voltage of 5V. The power requirement for reverse rotation with a 5V source is 1.47 watts on the reverse button, while a 12V source requires 1.69 watts.